2015
DOI: 10.5114/wiitm.2015.52556
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo pyelotomy, nephroscopy and holmium laser lithotripsy of a staghorn stone in a donor kidney prior to renal transplant.

Abstract: This case report presents the diagnostic and treatment procedures of stone removal from the kidney of a 67-year-old donor, the transplantation of the kidney to a 65-year-old recipient, and the postoperative course until the end of hospitalization. Computed tomography performed before collecting the organ showed a staghorn stone in the renal pelvis and lower calyces in the right donor kidney. The stones were removed ex-vivo using a rigid ureteroscope and a holmium laser prior to transplantation. Then the organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…[ 6 ] suggested that extracorporeal shock wave lithotripsy (ESWL) could be performed on donor before transplantation, while Trivedi [ 7 ] and Devasia [ 8 ] confirmed the efficacy of ESWL after transplantation. Rashid [ 9 ], Janczak [ 10 ] and Vasdev [ 11 ] reported extracting calculi from excised donor kidney using URS, flexible URS and pyelolithotomy, respectively, all of which achieved satisfying outcome. The feasibility of URS lithotripsy and percutaneous nephrolithotomy (PCNL) on donor kidney graft after transplantation was confirmed by Benooit [ 12 ] and Krambeck [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] suggested that extracorporeal shock wave lithotripsy (ESWL) could be performed on donor before transplantation, while Trivedi [ 7 ] and Devasia [ 8 ] confirmed the efficacy of ESWL after transplantation. Rashid [ 9 ], Janczak [ 10 ] and Vasdev [ 11 ] reported extracting calculi from excised donor kidney using URS, flexible URS and pyelolithotomy, respectively, all of which achieved satisfying outcome. The feasibility of URS lithotripsy and percutaneous nephrolithotomy (PCNL) on donor kidney graft after transplantation was confirmed by Benooit [ 12 ] and Krambeck [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of treating transplant kidney extracorporeally are as follows: (i) abides by the ‘absolute sound’ principle of medical ethics; (ii) ensures the quality of donor kidney by reducing operation difficulty, surgery time and additional damage; (iii) abides by the maximum benefit principle of medical ethics and avoids the long-term risk of calculus in the recipient. Therefore, we are more inclined to the strategy used by Rashid [ 9 ] and Janczak [ 10 ], which is URS or flexible URS combining holmium laser lithotripsy on extracorporeal donor kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Calculi located in the pelvicalyceal system, which are a rare clinical problem in donor kidneys, are a relative contraindication to kidney transplantation. Because of the grafts shortage and the development of contemporary endourological techniques, successful management has been achieved [ 1 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calculi in donor kidneys always constitute a significant clinical challenge. Because of the grafts shortage, many attempts have been made to treat calculi in donor kidneys, and many have achieved successful management [ 1 4 ]. To the best of our knowledge, this case report is the first to present removal of stones from bilateral kidneys from a single donor through flexible ureteroscopy before transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, there was also pelvic necrosis, so the reason for the complication was due to blood supply, not the method of nephrectomy. Some authors also reported ex vivo procedures before transplantation – varying from simple vascular reconstruction to complex procedures of pyelotomy with laser lithotripsy due to staghorn stone [ 18 ]. In our group thanks to very good donor selection, apart from arterial reconstruction no other ex vivo procedures were necessary.…”
Section: Discussionmentioning
confidence: 99%